The PLC Book. - Dana, Nancy Fichtman (SAGE Publications, 2015)
The secret to your PLC's success? You. Commitment to improving student outcomes is a natural part of being a teacher-and that's why this book is for every member of the team, not just the leader. When you bring your experience, skills, and questions to a professional learning community, you help shape its future. You'll work collaboratively to Give voice to important issues and dilemmas Decide where to focus your work Develop and implement a plan for gaining insight into your area of focus Take action based on individual and collective learning Share results with others outside the PLC.